2014
DOI: 10.3171/2012.12.focus12351
|View full text |Cite
|
Sign up to set email alerts
|

The Cancer Genome Atlas expression profiles of low-grade gliomas

Abstract: Differentiating between low-grade gliomas (LGGs) of astrocytic and oligodendroglial origin remains a major challenge in neurooncology. Here the authors analyzed The Cancer Genome Atlas (TCGA) profiles of LGGs with the goal of identifying distinct molecular characteristics that would afford accurate and reliable discrimination of astrocytic and oligodendroglial tumors. They found that 1) oligodendrogliomas are more likely to exhibit the glioma-CpG island methylator phenotype (G-CIMP), relative to low-gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“…cancer stem cell versus regular cancer cells; see below for more details). A study comparing the expression of miR-126 in oligodendroglioma and astrocytoma (24 patients: two WHO grade II and 22 WHO grade III) found that astrocytomas expressed less miR-126 than oligodendrogliomas (fold change=0.479) (23). Lately, miR-126, miR-137 and miR-128 were found to be most overexpressed in non-differentiated glioblastoma spheroid cultures containing stem cell-like tumor .…”
Section: Discussionmentioning
confidence: 99%
“…cancer stem cell versus regular cancer cells; see below for more details). A study comparing the expression of miR-126 in oligodendroglioma and astrocytoma (24 patients: two WHO grade II and 22 WHO grade III) found that astrocytomas expressed less miR-126 than oligodendrogliomas (fold change=0.479) (23). Lately, miR-126, miR-137 and miR-128 were found to be most overexpressed in non-differentiated glioblastoma spheroid cultures containing stem cell-like tumor .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the LLGs patients with IDH mutations and 1p/19q co-deletions had the most favourable clinical outcomes. Moreover, their gliomas harboured mutations in CIC, FUBP1, NOTCH1, and the TERT promoter [7], which are very consistent with as proposed by Gonda et al, [22].…”
Section: Tp53 Idh1 Idh2 Cic Fubp1 Pi3kc Egfr H3f3a Braf Ptensupporting
confidence: 74%
“…A cluster-of-cluster analysis of mRNA, copy number, microRNA (miRNA) and methylation analyses reinforced the clear separation of three molecular classes of LGG based on the status of IDH1/2 and 1p/19q [22]. These data illustrate a potential stratification of LGGs that emphasizes molecular characteristics.…”
Section: Tp53 Idh1 Idh2 Cic Fubp1 Pi3kc Egfr H3f3a Braf Ptenmentioning
confidence: 73%
See 2 more Smart Citations